2018
DOI: 10.18314/jnb.v4i1.1079
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Characteristics of Green Tea Polyphenols on Lipopolysaccharide-Stimulated RAW Cells

Abstract: The inflammatory response of macrophages is involved in pathogenesis of lifestyle-related diseases. Green tea consumption reduces the incidence of lifestyle-related diseases. This study investigated the anti-inflammatory effect of polyphenols of green tea including gallic acid, (+)-catechin, (-)-catechin, (-)-epicatechin and (-) epigallocatechin-3-gallate (EGCG) in vitro. The macrophage cell line RAW264 cells were pre-treated with different concentrations of polyphenols (gallic acid, (+)-catechin, (-)-catechin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Generally, the immune system lyses the bacteria and releases the lipid part of LPS into the circulation, which initiates endotoxic activity and triggers the release of pro-inflammatory mediators from macrophages [28,29]. Past experiments revealed that LPS-challenged macrophages excessively produced TNF-α and IL-6, along with other cytokines [30,31]. In order to suppress the activation of macrophages, adequate antioxidant supply is needed through the diet, which may further repair the damaged site [32].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the immune system lyses the bacteria and releases the lipid part of LPS into the circulation, which initiates endotoxic activity and triggers the release of pro-inflammatory mediators from macrophages [28,29]. Past experiments revealed that LPS-challenged macrophages excessively produced TNF-α and IL-6, along with other cytokines [30,31]. In order to suppress the activation of macrophages, adequate antioxidant supply is needed through the diet, which may further repair the damaged site [32].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the infiltration of macrophages and the production of inflammatory cytokines were shown to be suppressed by macrophage depletion [33]. We have, therefore, been studying the effects of exercise-induced anti-inflammatory effects to suppress the recruitment and activation of neutrophils and monocytes/macrophages as the sources of inflammatory mediators and ROS and in preventing exercise-induced tissue damage [5,9,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47].…”
Section: Chronic Inflammation and Anti-inflammatory Effects Of Exementioning
confidence: 99%
“…We have reported that an eight-week KD may increase intramuscular oxidative stress [69,71]. As mentioned below, certain supplementation such as green tea extract or polyphenols may alleviate exercise-induced oxidative stress, and those antioxidants may then contribute to the promotion of muscle health and exercise capacity [34,35,37,39,45,72,73]. In any case, some combined and/or restricted applications should be considered and explored.…”
Section: Some Challenging Countermeasures Of Exercise-induced Redumentioning
confidence: 99%
“…In this regard, Veillonella atypical, the abundance of which increases in response to exercise, has been demonstrated to enhance running time performance via its metabolism of lactate (Scheiman et al, 2019), whereas Akkermansia muciniphila, which is reduced in abundance in response to cold exposure, is known to be associated with intestinal gene expression promoting tissue remodeling and suppression of apoptosis via a currently unknown pathway (Chevalier et al, 2015). Besides, other components such as lipopolysaccharide of diet-induced obesity-related gut bacteria may promote inflammation (Boulangé et al, 2016), However, the obesity-related inflammation is reversed by exercise (Kawanishi et al, 2012), ketogenic diet (Ma et al, 2018), or food components such as green tea polyphenols (Hung et al, 2018), which might be due to certain modulations by the gut microbiome. Microbiota depletion has been shown to promote the browning of white adipose tissue and to reduce obesity (Suárez-Zamorano et al, 2015).…”
Section: Discussionmentioning
confidence: 99%